Persepsi Karyawan tentang Penerapan Analisis Jabatan - Sugiantoro, Billyawan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The aim of the research is to study the perception of the operational employees toward the result of functional analysis in Micro Banking District Center, Jakarta of PT Bank Mandiri, Tbk (Persero). The research is descriptive and uses quantitative approach. The data were collected by spreading questionnaires, using stratified random sampling technique. The result of the research shows that the perceptions of the Bank Mandiri’s employees toward functional analysis result is ranging “good”. However improvement in the aspects of compensation, facility completeness and compatibility, and educational suitability are still needed.